Gender Analysis of Armenian School Curriculum and Textbooks Policy Brief - Silova, Iveta (World Bank E-Library Archive, 2016)
The Armenian government has articulated the commitment to integrating the principles of gender equality in its education system. This commitment has been reflected in the adoption of the gender policy concept paper in 2010 and the law on securing equal rights and equal opportunities for women and men in 2013, which identify gender equality as a priority area and call for integrating the gender dimension into the school curriculum at all levels. This policy report examines whether and to what extent the principles of gender equality are reflected in Armenian school curriculum and textbooks, identifies key issues related to the achievement of gender equality goals in education, and provides policy level recommendations to improve gender-sensitivity in school curriculum and textbooks. Data was drawn from an overview of existing studies on gender representation in Armenian school curricula and textbooks conducted by local experts, primarily relying on the study commissioned by the World Bank (Osipov and Sargizova, 2015). The study was based on a comprehensive analysis of 9 high school textbooks in Social Science (grades 10 and 11), Armenian History (grades 10, 11 and 12), and Armenian Literature (grades 10, 11 and 12), as well as an analysis of academic standards, syllabi, and teacher's guides for the same subjects. Data for the policy report was also supplemented by interviews with key education stakeholders